GAMBARAN PERSEPSI ORANG TUA TENTANG VERBAL ABUSE PADA ANAK USIA SEKOLAH DI DUSUN JETIS PILANGSARI, KEC. NGRAMPAL, KAB. SRAGEN - Gunarsih; Dewi Kartika Sari (Nusantara Hasana Berdikari, 2022)
Verbal abuse is a violent behavior in the form of speech that can hurt emotionally and have a bad impact on children. Data shows that 62% of children experience violence, of which 3 out of 5 girls and half of all boys experience verbal abuse. The purpose is knowing the description of parents' perceptions of verbal abuse in school-age children in Jetis Hamlet, Ngrampal, Sragen. This research is descriptive research, with univariate analysis method. that the majority of mothers were 25-35 years old, namely 21 (66%). Characteristics of education as many as 13 (41%) mothers with high school education. Job characteristics as many as 14 (44%) mothers work as farmers. Mother's perception of verbal abuse in school-age children in Jetis Pilangsari Hamlet, the majority are in the good category, namely 32 (54%). The majority of mothers aged 25-35 years, the majority of mothers with high school education, the majority of mothers with farmer jobs. Mother's perception of verbal abuse in school-age children in the hamlet of Jetis Pilangsari, Ngrampal, Sragen are in the good category.